STUDENTS' NEED IN LANGUAGE TESTING AND EVALUATION SUBJECT AT THE ENGLISH DEPARTMENT OF UIN PROF. K. H. SAIFUDDIN ZUHRI PURWOKERTO - Irra Wahidiyati; Khoeriah Kholid (Wiralodra English Journal, 2025)
This descriptive quantitative study analyzed the students in the Language Testing and Evaluation (LTE) subject. The sources of information were taken from 100 students and two lecturers. Questionnaires and interviews are used to gain the data. From the result of the research, the students need detailed material about language testing and evaluation as their skills for being teachers in the future. First, they need explicit material about assessments and tests. Second, they need the material for creating listening, speaking, writing, and reading test items because there are some types of listening, speaking, writing, and reading that students should master. Next, the TBI (Tadris Bahasa Inggris) students must master creating listening, speaking, writing, and reading test items. The TBI student also needs information on creating assessment rubrics for listening, speaking, writing, and reading test items. In the interview with the lecturer, the TBI students need to understand all assessment components. The LTE lesson plan should state that a detailed assessment rubric has been added for each skill, even though making an assessment rubric per type of existing skill is necessary.